Personal Branding of Generation Z Through Jaipong Dance: A Case Study at Sanggar Seni Cahaya Kancana - Jihan Julyanti Yuhdi; Siti Komariah; Mirna Nur Alia Abdullah (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2025)
Generation Z faces increasing challenges in forming their sense of self. This study explores how traditional arts, particularly Jaipong dance, can serve as a medium for personal branding through informal learning. A qualitative case study approach was employed, with data collected via observation, in-depth interviews, and documentation of active members of Sanggar Seni Cahaya Kancana in Garut, West Java. The findings suggest that the studio serves as a social and cultural ecosystem where participants internalise cultural values, boost their self-confidence, and develop personal branding both offline and online. Specifically, participants demonstrated significant character development, gained community recognition, and used social media to amplify their cultural identities. The results support the integration of traditional art into youth identity formation by combining local heritage with digital expression. This study contributes to the understanding of informal learning spaces as strategic environments for shaping competitive and culturally grounded identities in the digital age